Giant staghorn common bile duct calculus: a case report - Bhattarai, Suraj Raj; Bhattarai, Abhisekh; Tamrakar, Kishor Kumar (Journal of Chitwan Medical College, 2019)
A bile duct stone is defined as large if it is more than 15mm in size and giant when it is 5cm or more. Giant staghorn calculi are usually uncommon but can be found in oriental cholangio-hepatitis and usually pigment stones. Bile infection appears to be the initial event leading to stone formation. The primary bile duct stones form within the bile ducts and usually of brown pigment type while secondary bile duct stones arise from gall bladder and intra or extra hepatic ducts. There are very few published reports which describe a giant staghorn calculus in the common bile duct (CBD). The purpose of this case report is to report a new rare case of giant staghorn CBD calculus and discuss the diagnostic and surgical approach because staghorn calculi are very rare in the biliary tract.